2021
DOI: 10.3389/fcell.2021.659731
|View full text |Cite
|
Sign up to set email alerts
|

FOXO4 Inhibits the Migration and Metastasis of Colorectal Cancer by Regulating the APC2/β-Catenin Axis

Abstract: Objective: Adenomatous polyposis coli 2 (APC2) is a colorectal cancer (CRC) tumor-suppressor gene. The progression of several kinds of cancer is closely associated with Forkhead box O4 (FOXO4). However, the function of FOXO4 in CRC is unclear. This study focused on the role of FOXO4 and the relationship between FOXO4 and APC2 in CRC migration and metastasis.Methods: The expressions of FOXO4, APC2, and p(S37)-β-catenin were detected in CRC tissues by immunohistochemistry, and their correlation was analyzed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…[9,27] Additionally, FoxO4 was reported to involve in healing of gastric ulcers induced by WRS through regulation of apoptosis and a decreased of APC2 and p(S37)-β-catenin positively correlated with FoxO4 also be reported, which suggests potential function of FoxO4 as tumor suppressor through upregulation of APC and Wnt/β-catenin pathway. [38,39] In our study, we similarly found that the expression of Keap-1 and FoxO4 was related with tumor differentiation. All these suggest potential relationship between aforementioned proteins with the severity and prognosis of CRC patients.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…[9,27] Additionally, FoxO4 was reported to involve in healing of gastric ulcers induced by WRS through regulation of apoptosis and a decreased of APC2 and p(S37)-β-catenin positively correlated with FoxO4 also be reported, which suggests potential function of FoxO4 as tumor suppressor through upregulation of APC and Wnt/β-catenin pathway. [38,39] In our study, we similarly found that the expression of Keap-1 and FoxO4 was related with tumor differentiation. All these suggest potential relationship between aforementioned proteins with the severity and prognosis of CRC patients.…”
Section: Discussionsupporting
confidence: 69%
“…[4] Furthermore, FoxO4 can inhibit expression of glucose transporter-1, erythropoietin, and vascular endothelial growth factor, which is crucial in tumor expansion and tumor progression. [37] Sun et al [38] also showed that FoxO4 overexpression substantially decreased CRC cells migration and in vivo metastasis. Consistent with these results, we also found that the expression of ALD, Keap-1, and FoxO4 were significantly associated with tumor location.…”
Section: Discussionmentioning
confidence: 99%
“…This reversal of expression might be an outcome of concomitant diabetes in ECD patients. Adenomatous polyposis coli protein 2 (APC) is a tumor suppressor protein that plays a role in cell migration, cell adhesion, proliferation, and differentiation It suppresses the Wnt/β-catenin pathway which is essential for epithelial–mesenchymal transition in many tumor cells . In human ovarian cells, downregulation of APC2 by miR-939 is required for cell proliferation .…”
Section: Discussionmentioning
confidence: 99%
“…However, whether miR‐3194‐5p promotes CRC progression by targeting galectin‐7 is worth further study. Among the various miR‐3194‐5p target genes predicted by the database, adenomatous polyposis coli 2, 36 KLF13, 37 and LDLRAD4 38 play anticancer roles in CRC. However, further study is required to determine whether miR‐3194‐5p promotes the occurrence and development of CRC through targeted inhibition of these genes.…”
Section: Discussionmentioning
confidence: 99%